Intelijen dan Diplomasi Internasional - Chairil, Tangguh (Global: Jurnal Politik Internasional, 2018)
The overlap between intelligence and diplomacy is one of the lost dimension of strategic intelligence and international relations studies, despite being crucial to understanding the politics among states. Departing from these considerations, this paper discusses the relationship between intelligence and diplomacy in the areas of how one affects another in a wider scope related to the states' efforts to meet their national interests. This paper also discusses how the activities of intelligence organizations complements and complicates diplomatic practice, and vice versa. From the discussions, this article concludes that there is a crucial overlap between intelligence and diplomacy in political relations among states, and there is a tendency that intelligence activities complicate the practices of diplomacy. Therefore, the relations between intelligence and international diplomacy requires more frequent and serious assessment.